Caminhos e possibilidades para a alfabetização de pessoas com surdocegueira congênita: a importância da formação docente - Falkoski, Fernanda Cristina (Universidade Federal de São Carlos, 2023)
The literacy of congenital Deafblind person is a little addressed topic that is little addressed nationally and internationally. This research intends to present paths and possibilities for the literacy of congenital Deafblind person, as well as the importance of teacher education. Therefore, the questions are: a) How does the literacy congenital Deafblind person happen in Brazil? and b) Does teacher education in Brazil support the choice of methodologies and strategies to be used in the literacy of congenital Deafblind students? To answer those questions the general objective is to identify and knowledge the possible ways for the literacy of congenital Deafblind students of different ages, from the report of experienced teachers who worked or have been working in the field in the last 10 years in Brazil. The research count on the participation of 9 teachers who had or has been literate congenital Deafblind students in Brazil. The methodology applied on this research is a descriptive exploratory approach, case study type. The participants were recruited through an exploratory questionnaire. In order to collect data, interviews were conducted, with the script that the questions were distributed in blocks to extract results on the follow situations: The teachers training; what they have done or are doing to literate the congenital Deafblind students; what resources they have or are using actually; which method is preferred or used; description of the methodology applied; others basic information about the procedure you have used or are using. Bardin content analysis was used for the data collected, and 10 categories of analysis were identified. In the results, we highlight the importance of initial and continuing education in relation to the literacy and Deafblindness for a successful intervention with students, and this pedagogical training being on job training. The research data mainly indicate that literacy is possible for the congenital deafblind person as long the teacher is prepared for it.
Paths and possibilities for literacy training for people with congenital deafblindness: the importance of teacher training
Keywords: Educação Especial; Surdocegueira congênita; Alfabetização; Formação continuada; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM